2022
DOI: 10.26468/trakyasobed.876452
|View full text |Cite
|
Sign up to set email alerts
|

Peri̇travmati̇k Stres Envanteri̇ (Pdi) Türkçe Geçerli̇k Ve Güveni̇rli̇k Çalişmasi

Abstract: Bu çalışmada Peritravmatik Stres Envanterinin (PDI) Türkçeye çevrilerek geçerlik ve güvenirliğinin incelenmesi amaçlanmıştır. Araştırmanın örneklemini 18-65 yaş grubunda yer alan 377 kişi oluşturmaktadır. Ölçeğin Türkçe formunun geçerlilik ve güvenirlik analizleri travmatik olay yaşadığını belirten 224 katılımcı üzerinden, karşılaştırma analizleri ise tüm katılımcılar (377) dahil edilerek yapılmıştır. Katılımcılara, PDI Türkçe versiyonunun yanı sıra Demografik Bilgi Formu ve Olayların Etkisi Ölçeği uygulanmışt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Scores can range from 0 to 52 with higher scores indicating more distress. The Peritraumatic Distress Inventory was translated into Turkish by Çağlar et al (2022) and the authors reported good internal consistency. Internal reliability of the scale scores was excellent (α = .90).…”
Section: Methodsmentioning
confidence: 99%
“…Scores can range from 0 to 52 with higher scores indicating more distress. The Peritraumatic Distress Inventory was translated into Turkish by Çağlar et al (2022) and the authors reported good internal consistency. Internal reliability of the scale scores was excellent (α = .90).…”
Section: Methodsmentioning
confidence: 99%